The Role of Dukun Suwuk and Dukun Prewangan in Curing Diseases in Kediri Community - Arini, Ratih Tyas; Alimi, Moh Yasir; Gunawan, Gunawan (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2016)
Finding a cure when people get sick is an important thing. One ofÂ  the efforts done by Kediri people in finding for a cure is to come to a Dukun (Shaman/traditional healer) Suwuk and Dukun Prewangan. The purposes of this research are to know the profiles and methods of Dukun Suwuk and Dukun Prewangan, and their role in curing diseases. This research used descriptive qualitative method. The results of this research show that (1) the process of healing and problem solution performed by Dukun Suwuk uses prayer as a key source of power. And Dukun Prewangan uses the help of supernatural beings who become their working partners to cure or resolve the problem, (2) Dukun Suwuk and Dukun Prewangan has an important role in society because of their presence is needed and respected. In addition, Dukun Suwuk and Dukun Prewangan who have been offering the services had experienced a lot of things as a living experience, (3) healing process performed by Dukun Suwuk and Dukun Prewangan is one solution for patients to be free from the ambiguous conditions of liminal stage. Choosing to go to a traditional healer healing is a rational choice for each patient.